AUTHORITARIAN BARGAIN IN BELARUS: THE SYSTEM OF SOCIAL BENEFITS AS A FACTOR OF REGIME STABILITY - PRANEVIČIŪTĖ-NELIUPŠIENĖ, JOVITA; MAKSIMIUK, ZHANNA (Politologija, 2012)
The article examines the possible reasons for regime stability in Belarus through the concepts of social contract and authoritarian bargain, arriving at the proposition that the extensive social welfare system in Belarus is the key to understanding the stability of the system over years. In academic literature, social and welfare policies are among the least researched factors of Belarus regime stability. The article summarizes theoretical findings on the use of social policies in authoritarian regimes and provides a detailed review of the structure and development of the social welfare system in Belarus. It is concluded that due to extensive social and welfare policies, the Belarusian regime manages to maintain social support at the level which is minimal but enough to keep stability in society and the political elite unchanged.